Taming the Glitter Ball: A Diagnosis of Shakespeare ‘for all time’—Sketched from South Africa - Wright, Laurence (Multicultural Shakespeare: Translation, Appropriation and Performance, 2023)
Shakespeare travels the globe more variously and unpredictably than any other dramatist. In performance his texts have shown themselves hospitable to vastly different ideological interpretations. By making these two points, I do not mean that Shakespeare pops up around the globe, sometimes in quite extraordinary guises, without rhyme or reason. Far from it. Where Shakespeare makes his appearance this is an act of deliberate choice, by a producer, a production company, an arts foundation, a school or university, a national arts authority, or even simply an ad hoc group of Shakespeare enthusiasts. His advent is always intentional, and often contextually explicit, whatever the rationale. But the sheer variety of guises in which his work appears, the disparate cultural and ideological vogues that attach to his work, the geographical spread of art pieces, performances and installations based on Shakespeare, not to mention the diverse artistic disciplines which seize on him as an inspiration, calls for explanation. No other artist in any medium exhibits comparable artistic fertility across time and space. To claim the limelight for more than 400 years without any sign of diminution is remarkable. This article seeks to understand why this ubiquity is possible. Specifically, is there a definable textual mechanism underlying his historical and international success? At the outset it should be indicated that this paper focuses on a technical diagnosis of textual prerequisites for Shakespeare’s international success. It is not about what his plays say or mean, and only incidentally about the values they exemplify. While the paper sets out to describe textual features which make possible some of his manifold theatrical enchantments, there is no intention to describe, evoke, or celebrate those enchantments.